A Scoping Review on the Use of Antibiotic-Impregnated Beads and Applications to Vascular Surgery. (February 2020) - McGuinness, Brandon; Ali, Khatija Pinky; Phillips, Steven; Stacey, Michael
Introduction: Surgical site infection (SSI) presents a ubiquitous concern to surgical specialties, especially in the presence of prosthetic material. Antibiotic-impregnated beads present a novel and evolving means to combat this condition. This review aims to analyze the quality of evidence and methods of antibiotic bead use, particularly for application within vascular surgery. Methods: A systematic scoping review was conducted within Embase, MEDLINE, and the Cochrane Registry of Randomized Controlled Trials. Articles were evaluated by 2 independent reviewers. Level of evidence was evaluated using the Oxford Center for Evidence-Based Medicine Criteria and the Cochrane Risk of Bias Tool for Randomized Controlled Trials. Results: The search yielded 6951 papers, with 275 included for final analysis. Publications increased in frequency from 1978 to the present. The most common formulation was polymethyl methacrylate; however publications on biodegradable formulations, including calcium sulfate beads, have been published with increasing frequency. Most publications had positive conclusions (94.2%); however, the data was mainly subjective and may be prone to publication bias. Only 11 randomized controlled trials were identified and all but one was evaluated to be at a high risk of bias. The most common indication was for osteomyelitis (52%), orthopedic prosthetic infections (20%), and trauma (9%). Within vascular surgery, beads have been used primarily for the treatment of graft infection, with freedom from recurrence rates being reported from 41% to 87.5%. Conclusions: Antibiotic-impregnated beads provide a means to deliver high doses of antibiotic directly to a surgical site, without the risks of parenteral therapy. There has yet to be significant high-level quality data published on their use. There is a large body of evidence that suggests antibiotic beads may be used in SSIs in high-risk patients, prosthetic infections, and other complex surgical infections. Important potential areas of application in vascular surgery include graft infection, prevention of wound infection in high-risk patients, and diabetic foot infection.